Impact evaluation of the indoor environmental performance of animate spaces in buildings. (December 2015) - Li, Junjie; Song, Yehao; Lv, Shuai; Wang, Qingguo
Abstract: Passive design has been widely identified as one of the most economical and effective strategies for sustainable building. The use of "animate" building space is one significant passive strategy in architectural design. It has two properties -organic and dynamic–and its type includes such as atriums, courtyards, wind towers, light wells, patios, sunspaces, etc. This study introduces a logical, scientific method of assessing building space performance. A multi-criteria approach was developed to validate and optimize the influence of animate spaces on sustainable buildings, with an emphasis on their influence on building environment quality and occupant satisfaction. Considering both the relationship between the building and people, and the building and the environment, and focusing primarily on of building design and building environment control, this research introduces an evaluation tool called SCTool. SCTool includes compasses that measure occupant satisfaction and indoor physical environment performance, and a Satisfaction–Comfort matrix that evaluates the fluctuating performances of animate spaces and the building's overall sustainable performance in building operating phase. This research chose atrium to represent one of typical animate spaces, and adopted a pair-group analysis method to isolate and analyze a single variable. Four typical atriums were chosen and divided into two categories: 3-direction atriums and high rise building atriums. Each test group of buildings included one green building and one conventional building. The results indicate the level of environmental performance of each object building, and highlight optimized possibilities for the atrium and the entire building in both the design and renovation phases. Highlights: Define the meaning of animate space and its boundaries. Set up a logical, scientific method to study the value of the animate space. Development of SCTool to assess animate space performance. Development of a pair-group analysis method to isolate and analyze a single variable. Repeatedly prove complex and dynamic adjustment of atrium space.